EVALUASI PENGGUNAAN LYSIMETER UNTUK MENDUGA EVAPOTRANSPIRASI STANDAR DAN EVAPOTRANSPIRASI TANAMAN KEDELAI (Glycine max (L) Merril) - Fadhilatul Adha; Tumiar Katarina Manik; R.A. Bustomi Rosadi (Teknotan: Jurnal Industri Teknologi Pertanian, 2016)
The purpose of this research was to evaluate estimating method of standard evapotranspiration and crops evapotranspiration using lysimeter than be compared with estimation result of evaporimeter pan and Penman – Monteith model who recommendated by FAO.  Standard evapotranspiration was estimated using reference crops and crops evapotranspiration was estimated using soybean Kaba varieties which planted in lysimeters. Rainfall data and standard evapotranspiration of evaporimeter pan be obtained from Agroclimate stations of Masgar in Pesawaran distric in Lampung, and evapotranspiration Penman – Monteith model was estimated by CROPWAT using climate data during 2007 – 2011 from Agroclimate stations of Masgar. The estimating result of standard evapotranspiration and crops evapotranspiration using lysimeter were higher than evaporimeter pan and model. The estimation results of standard evapotranspiration and crop evapotranspiration of Lysimeter was higher than the estimation evaporimeter pan and model. The average of standard evapotranspiration during nine dasarian is  6.14 mm/day, average of crop evapotranspiration is 7.54 mm/day, while the standard evapotranspiration of evaporimeter pan is 3.55 mm / day, and standard evapotranspiration estimation results with CROPWAT for November to February are 3.27; 3.20; 3.63; 3.51 mm/day. Crop coefficient (Kc) estimation results of each phase was 0.96 in the initial phase, 1.16 in the development phase, 1.67 in the mid season phase, and 1.18 at the end season phase. Crop coefficient (Kc) Soybean lysimeter estimation results are higher than FAO Crop coefficient recommendation. However observed from the growth and yield of soybean plants seen their best with 10.73 gr of 100  seeds of yield. So that suggested for further research with direct ETo measurement method can be applied with modification or regenerated of lysimeter specifications and construction to consider other parameters of water balance in lysimeter.keywords :  standard evapotranspiration, crops evapotranspiration, lysimeter, soybean